2012
DOI: 10.1016/j.bbamcr.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-ERK MAPK regulatory network controls dedifferentiation in Caenorhabditis elegans germline

Abstract: How a committed cell can be reverted to an undifferentiated state is a central question in stem cell biology. This process, called dedifferentiation, is likely to be important for replacing stem cells as they age or get damaged. Tremendous progress has been made in understanding this fundamental process, but its mechanisms are poorly understood. Here we demonstrate that the aberrant activation of Ras-ERK MAPK signaling promotes cellular dedifferentiation in the Caenorhabditis elegans germline. To activate sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…S2A-G), this activation should not be an indicator of these cells being at the meiotic stage. Rather, this activation in the distal region could be one of the causes of the decreased germ cell number phenotype that we observed in cdd-1/2 DKO germlines based on the known role of MPK-1 in inhibiting germline proliferation (Lee et al 2006;Cha et al 2012). To confirm this, we found that reducing mpk-1 activity by RNAi in cdd-1/ 2 DKO animals increased germ cell number in the mitotic zone (Fig.…”
Section: Glp-1 Expression In the Distal Gonad Region Is Repressed By supporting
confidence: 63%
“…S2A-G), this activation should not be an indicator of these cells being at the meiotic stage. Rather, this activation in the distal region could be one of the causes of the decreased germ cell number phenotype that we observed in cdd-1/2 DKO germlines based on the known role of MPK-1 in inhibiting germline proliferation (Lee et al 2006;Cha et al 2012). To confirm this, we found that reducing mpk-1 activity by RNAi in cdd-1/ 2 DKO animals increased germ cell number in the mitotic zone (Fig.…”
Section: Glp-1 Expression In the Distal Gonad Region Is Repressed By supporting
confidence: 63%
“…In this system, the key mediators of the mitosis-meiosis transition are PUF (Pumilio and FBF) RNA-binding proteins, and removal of the PUF-8 protein leads to formation of germline tumors that derived from primary (and occasionally secondary) spermatocytes. Interestingly, the mild phenotype of the PUF-8 mutants is greatly enhanced by the activation of the MAPK pathway [63], probably by promoting both dedifferentiation and proliferation. We envisage that a similar process, although relying on the concerted activation of different mitosis-meiosis regulators present on specific chromosomes, may also be operating in the mammalian testis.…”
Section: Discussionmentioning
confidence: 99%
“…1B). This Ras-ERK/MAPK signaling pathway controls multiple cellular processes, including induction of vulval, uterine, spicule, P12 and excretory duck cell fates, control of sex myoblast migration and axon guidance, as well as regulation of germline stem cells and their differentiation [11,13,12,14]. Particularly, Ras-ERK/MAPK signaling pathway controls the self-renewal and differentiation of GSCs, depending on the genetic context: MPK-1/ERK activation promotes the proliferation of GSCs in puf-8; gap-3 mutant background [15], but it also promotes the differentiation of GSCs in wild-type [14] and puf-8; lip-1 mutant background [16].…”
Section: Introductionmentioning
confidence: 99%